Barthes deliberates: Pascal, Ignatius and the question of the diary. Issue 2 (23rd February 2016) - Knight, Diana
Abstract : This article traces the interconnections between the rhetoric and actuality of Barthes's proclaimed inability to choose between the polarised forms of Album and Book, of fragmentary Diary and all-embracing Novel. In The Preparation of the Novel, his pedagogical rehearsal of this indecision is structured as the theatrical 'deliberation' of the writer faced with the relentless obligation to choose. Yet Barthes underlines the appeal of thinking in terms of simplified alternatives, and leaves the crucial formal decision hanging in the balance. I read this artificially constructed deliberation in conjunction with Barthes's 1969 analysis of Ignatius's Spiritual Exercises, where a new language through which to solicit God's will is elaborated through the theatrical preparation of an 'election'. While Ignatius's Exercises prepare the question (the need to decide between two equally weighted choices of action), its divine response is to be found in his Spiritual Diary . The symbiotic relation that Barthes identifies between the pedagogical Exercises and the personal Diary (in which Ignatius charts the progress of a practical election), takes me to the relation between Barthes's lecture course and his own private diaries. His 1979 essay 'Deliberation' combines a general question (can a Diary be Literature?) with a practical issue: should Barthes keep a diary with a view to publication? While 'Deliberation' works through a set of pros and cons to establish the Diary's claim to a value on a par with the Novel, Barthes's personal dilemma is left unresolved. This, I suggest, is because his more clandestine election concerns a decision over whether to publish the 1977 Journal d'Urt, of which extracts are experimentally embedded as exempla within the rhetorical structure of 'Deliberation' itself.